Analysis Behavior Consumer Regarding Product Purchase Interest Processed Pond Fish In Traditional Markets Regency Lamongan - Bhiaztika Ristyanadi; Luluk Nur Azizah; Suyoto, Suyoto (SEAN Institute, 2024)
Study This aim For analyze characteristics and behavior consumer as well as analyze connection between influencing factors behavior consumer to decision consumer buy product processed fish in traditional markets. Study This carried out from May to June 2024 in traditional markets regency Lamongan. Method used is method studies case. Retrieval technique sample use method accidental sampling with amount respondents in study This 109 respondents. Analysis data use model regression linear multiple with SPSS. In study This variable free covers culture (X1), social (X2), personal (X3), psychology (X4), price (X5), income (X6), quantity dependents (X7), and tastes (X8). Variable bound is decision buy (Y). Variable free in a way simultaneous influential significant to decision purchase product processed fish. Whereas in a way Partial factors that are significant influence decision buy product processed fish is factor culture (X1), factor psychological (X4), factor price (X5), factor income (X6), factor dependent (X7), and taste factors (X8). Behavioral factors the most dominant consumer influence decision buy product processed fish at traditional markets in the district Lamongan is factor psychological (X4).